(untitled) (World Bulletin of Social Sciences, 2024)
The composition of proper names in any language is not given once and for all. The repertoire of anthroponyms is changing: some disappear from active use, others are created, and others change their place. Anthroponymy is a section of onomastics that studies anthroponyms (from the Greek anthropos - person and onoma - name) - names of people: personal names, patronymics, surnames, nicknames, pseudonyms, encrypted names, etc.